2018
DOI: 10.1002/jcp.26768
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian cancer stem cell: A potential therapeutic target for overcoming multidrug resistance

Abstract: The cancer stem cell (CSC) model encompasses an advantageous paradigm that in recent decades provides a better elucidation for many important biological aspects of cancer initiation, progression, metastasis, and, more important, development of multidrug resistance (MDR). Such several other hematological malignancies and solid tumors and the identification and isolation of ovarian cancer stem cells (OV-CSCs)show that ovarian cancer also follows this hierarchical model. Gaining a better insight into CSC-mediated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 155 publications
1
36
0
1
Order By: Relevance
“…Ovarian cancer is an umbrella term for a broad range of neoplasms of different histopathological types, including serous, endometrioid, clear cell, and mucinous; importantly, these subtypes exhibit different responses to drug treatment [89]. The proportion of CSCs in ovarian cancer varies between 0.1% and 30% depending on the disease type and stage [90].…”
Section: Csc-targeting Therapiesmentioning
confidence: 99%
“…Ovarian cancer is an umbrella term for a broad range of neoplasms of different histopathological types, including serous, endometrioid, clear cell, and mucinous; importantly, these subtypes exhibit different responses to drug treatment [89]. The proportion of CSCs in ovarian cancer varies between 0.1% and 30% depending on the disease type and stage [90].…”
Section: Csc-targeting Therapiesmentioning
confidence: 99%
“…Despite substantial improvements in treatment of ovarian cancer in the past several decades, the prognosis of ovarian cancer patients is still dismal, which is largely attributed to chemotherapeutic resistance after a long period of treatment. Cancer stem cells (CSCs) that are a minority population of cells with the abilities of unrestrained proliferation and self-renewal have been identified to contribute to the failure of chemotherapy in ovarian cancer patients 2, 3. Several lines of evidence have reported that CSCs are crucial mediators in the induction and maintenance of chemotherapeutic resistance in several human cancers,4, 5 including ovarian cancer 6, 7.…”
Section: Introductionmentioning
confidence: 99%
“…Çoklu ilaç direnci (ÇİD) kemoterapinin etkisini azaltan en büyük sorunlardan biridir ve hücre içi ilaç alıkonmasının düşük olması, hücre dışına ilaç akışının artması, detoksifikasyon sistemlerinin aktivitesi, gelişmiş DNA onarım mekanizmaları ve kusurlu apoptoz gibi nedenlerle ortaya çıkmaktadır. Kanser hücrelerindeki çoklu ilaç direncinin kemoterapi ilaçlarını hücreden dışarı pompalayıp hücre içi ilaç konsantrasyonunu azaltan P-glikoproteinlerin (P-gp) aşırı ekspresyonu ile ilişkili olduğu gösterilmiştir [1][2][3][4][5]. İlacın serum dozunun artırılması çoklu ilaç direncine bir çözüm olsa da aynı zamanda normal dokular üzerinde de toksik etkilerin açığa çıkması kaçınılmazdır.…”
Section: Gi̇ri̇ş (Introduction)unclassified